Using the quadratic formula, we can solve for x:
x = (-b ± √(b^2 - 4ac))/(2a)
In this case, a = 2, b = 8, and c = -10. Substituting these values into the quadratic formula, we get:
x = (-8 ± √(8^2 - 4(2)(-10)))/(2(2))
x = (-8 ± √(64 + 80))/4
x = (-8 ± √(144))/4
x = (-8 ± 12)/4
This gives us two solutions:
x = (-8 + 12)/4 = 4/4 = 1
x = (-8 - 12)/4 = -20/4 = -5
Therefore, the correct answer is: c. x = –5, 1
Solve for x.
2x2 + 8x – 10 = 0
(1 point)
a. x = –5, 2
b. x = 5, –2
c. x = –5, 1
d. x = 5, –1
1 answer